Determinants of gastro-oesophageal reflux perception in patients with persistent symptoms despite proton pump inhibitors. Issue 2 (19th October 2007) - Zerbib, F; Duriez, A; Roman, S; Capdepont, M; Mion, F
Abstract : Background and aim: Approximately 20% of patients have persistent symptoms of gastro-oesophageal reflux despite proton pump inhibitor (PPI) therapy. The aim of this study was to assess the determinants of reflux perception in patients on PPI therapy. Patients and methods: 20 patients with typical gastro-oesophageal reflux symptoms (heartburn and/or regurgitation) despite double-dose PPIs (twice daily) were included in this study. Ambulatory 24 h pH–impedance studies were performed in all patients. The characteristics of symptomatic and asymptomatic reflux episodes were compared. Symptoms were considered globally and separately for heartburn and regurgitation. Results: A total of 1273 reflux episodes were detected including 243 (19.1%) acidic, 1018 (80.0%) weakly acidic and 12 (0.9%) weakly alkaline reflux episodes. Overall, 312 (24.5%) reflux episodes were symptomatic. The only factor associated with reflux perception was high proximal extent (p = 0.037). Compared with regurgitation, reflux episodes associated with heartburn were more frequently pure liquid (p = 0.009) and acidic (p = 0.027), had a lower nadir pH (p<0.001), were more frequently preceded by acid reflux episodes (p<0.001) and had a longer reflux bolus clearance time (p<0.001). Conclusions: High proximal extent of the refluxate is the only factor associated with reflux perception in patients on double-dose PPI. However, compared with regurgitation, composition of the refluxate, sensitisation of the oesophagus by preceding acid exposure and delayed bolus clearance appear to play a role in heartburn perception.